2021
DOI: 10.1002/ange.202015411
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Spiro‐Axis Induced Blue Thermally Activated Delayed Fluorescence Material for Efficient Circularly Polarized OLEDs with Low Efficiency Roll‐Off

Abstract: A spiro‐axis skeleton not only introduces circularly polarized luminescence (CPL) into thermally activated delayed fluorescence (TADF) molecules but also enhances the intramolecular through space charge transfer (TSCT) process. Spiral distributed phenoxazine and 2‐(trifluoromethyl)‐9H‐thioxanthen‐9‐one‐10,10‐dioxide act as donor and acceptor units, respectively. The resulting TADF enantiomers, (rac)‐OSFSO, display emission maxima at 470 nm, small singlet‐triplet energy gap (ΔEST) of 0.022 eV and high photolumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…Moreover, the g lum of (R)-SDMAC and (S)-SDMAC is up to À 1.19 × 10 À 3 and + 1.39 × 10 À 3 , respectively (Figure 4D), which is consistent with most CP-TADF molecules reported in the literature. [6,32,60,61] We also tested the enantiomeric excess and CPL properties of the sample after sublimation and found that they were consistent with the properties before sublimation (Figures S21-S23).…”
Section: Theoretical Calculationsmentioning
confidence: 66%
“…Moreover, the g lum of (R)-SDMAC and (S)-SDMAC is up to À 1.19 × 10 À 3 and + 1.39 × 10 À 3 , respectively (Figure 4D), which is consistent with most CP-TADF molecules reported in the literature. [6,32,60,61] We also tested the enantiomeric excess and CPL properties of the sample after sublimation and found that they were consistent with the properties before sublimation (Figures S21-S23).…”
Section: Theoretical Calculationsmentioning
confidence: 66%
“…34 The HOMO energy levels were obtained via the oxidation potential of each complex using the equation of E HOMO = −[ E OX − E (Fc/Fc+) + 4.8] eV and estimated to be −5.61 and −5.62 eV for (4tfptp) 2 Ir(tpip) and (4tfptp) 2 Ir(Stpip), respectively. 35 The energy level gaps ( E gap ) of (4tfptp) 2 Ir(tpip) and (4tfptp) 2 Ir(Stpip) complexes were calculated from the UV-vis absorption spectra as 2.14 and 2.24 eV, respectively (Table 1). Therefore, the LUMO energy levels were estimated as −3.47 and −3.38 eV for (4tfptp) 2 Ir(tpip) and (4tfptp) 2 Ir(Stpip), respectively, with the equation of E LUMO = E HOMO + E gap .…”
Section: Resultsmentioning
confidence: 99%
“…The high kRISC values of 1-5 indicate that they can efficiently consume triplets for emission, alleviating triplet-triplet/triplet-polaron annihilations [48][49][50][51]. By broadening the recombination zones with optimized device structures, the efficiency roll-offs would be suppressed [35,36]. The high device efficiencies indicate that 1-5 are promising functional materials for high-performance EL devices.…”
Section: Resultsmentioning
confidence: 99%
“…Recent researches have proved that cofacial D/A alignments are favored for developing efficient TSCT emitters [25][26][27][28][29][30][31][32][33][34][35][36][37][38], which can reinforce TSCT and promote radiative decay of charge-transfer states [35,37]. Very recently, Jiang and Liao et al…”
Section: Introductionmentioning
confidence: 99%